In Vitro Anti-Oxidant and Anti-Microbial Study On Cassia Auriculata Linn. - M. THAMBIDURAI; P. RAJESH; B. BALAMURUGAN; V. RAJESH KANNAN (International Journal of Pharma and Bio Sciences, 2010)
The extensive list of disorders and pathogenesis in which radicals and oxidants have been implicated is still growing. From the past decades the herbal products are widely used in traditional and ayurvedhic formulations. The herbal products probably have not shown any sign of toxic to human beings also with lesser or no side effects. The study was intended to evaluate the in-vitro antioxidant and antimicrobial activity of methanolic extract of Cassia auriculata Linn. (MECA) in leaves, fruits and flowers were determined and each extracts was measured using three different methods of nitric acid radical, DPPH (1,1-diphenyl-2-picrylhydrazyl) and hydrogen peroxide scavenging assay while the ascorbic acid and rutin were used as standard and positive control for the analysis. Further they have studied about the flavonol content and antimicrobial activity in different strains. The MECA had shown the significant activity in all the methods when compared to the standard antioxidants i.e., ascorbic acid, rutin. Eventhough, among the three methods and different extract, the fruits of MECA showed that maximum reducing power of inhibition in the investigation also fruit MECA found that 46.1% in nitric acid, 69.5% in DPPH, 79.0% in hydrogen peroxide method. The antioxidant activity was confirmed by the presence of the flavonoids presence hence the flavonol content also measured in the content and showed 18.55%. Methanol extract of fruits of C. auriculata showed the highest antioxidant activity while the methanol extract of leaves and flowers of C. auriculata possessed the lowest antioxidant activity. However, the finding showed that most of the tested extracts were showing strong antioxidant activity even higher than the ascorbic acid and rutin.